2012
DOI: 10.1016/j.bpj.2012.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Protein Interactions in Calcium Transport Regulation Probed by Saturation Transfer Electron Paramagnetic Resonance

Abstract: We have used electron paramagnetic resonance (EPR) to probe the homo- and heterooligomeric interactions of reconstituted sarcoplasmic reticulum Ca-ATPase (SERCA) and its regulator phospholamban (PLB). SERCA is responsible for restoring calcium to the sarcoplasmic reticulum to allow muscle relaxation, whereas PLB inhibits cardiac SERCA unless phosphorylated at Ser(16). To determine whether changes in protein association play essential roles in regulation, we detected the microsecond rotational diffusion of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 78 publications
5
35
1
1
Order By: Relevance
“…S12). Specifically, the significant change in Cα shift with respect to free PLN AFA is a strong indicator of SERCA binding and confirms that the TM domain remains bound to SERCA on phosphorylation, as recently demonstrated by EPR spectroscopy (17). When monitored by rINEPT experiments, the intensities of the 13 C resonances of PLN pS16AFA domain Ia in the free form are much higher than those of the unphosphorylated PLN AFA , a finding indicative of an order-to-disorder transition on phosphorylation (SI Appendix, Fig.…”
Section: Mapping Of Serca/pln Interactions By Paramagnetic Relaxationsupporting
confidence: 82%
See 1 more Smart Citation
“…S12). Specifically, the significant change in Cα shift with respect to free PLN AFA is a strong indicator of SERCA binding and confirms that the TM domain remains bound to SERCA on phosphorylation, as recently demonstrated by EPR spectroscopy (17). When monitored by rINEPT experiments, the intensities of the 13 C resonances of PLN pS16AFA domain Ia in the free form are much higher than those of the unphosphorylated PLN AFA , a finding indicative of an order-to-disorder transition on phosphorylation (SI Appendix, Fig.…”
Section: Mapping Of Serca/pln Interactions By Paramagnetic Relaxationsupporting
confidence: 82%
“…Moreover, there have been few structural data on the complex between SERCA and phosphorylated PLN. On the basis of crosslinking and sparse spectroscopic data, two different mechanistic models have been proposed: a dissociative model, in which phosphorylation causes PLN detachment from SERCA, reestablishing Ca 2+ flux (14), and the subunit model, in which phosphorylation induces conformational rearrangements of PLN's cytoplasmic domain without dissociation (15)(16)(17). Nevertheless, the two models fall short in the interpretation of the recent structure-function correlations (15,(18)(19)(20).…”
mentioning
confidence: 99%
“…The effect is presumably caused by structural features of mitochondrial CK, particularly the existence of a sulfhydryl group in the active center which is probably not present in the cytosolic isoforms (Wyss & Kaddurah-Daouk 2000). So, the obtained results could be caused by oxidative modifications of the enzyme (James et al 2012), although a lower rate of enzyme synthesis cannot be excluded as another cause. …”
Section: Discussioncontrasting
confidence: 46%
“…β-adrenergic-mediated phosphorylation of PLB at S16 by PKA, or at T17 by CaMKII, partially restores SERCA2a activity (Bers 2002; Karim et al 2006; Wegener et al 1989). Recent studies show that PLB remains bound to SERCA2a, even after phosphorylation (Dong and Thomas 2014; James et al 2012), so SERCA2a activity can be restored only by phosphorylating PLB, ablating PLB, overexpressing SERCA2a, or expressing a loss-of-inhibition mutant of PLB.…”
Section: Introductionmentioning
confidence: 99%
“…This model further validated the strategies of decreasing PLB expression and increasing PLB phosphorylation, and it motivated the search for a drug that uncouples PLB from SERCA2a (Cornea et al 2013; Ferrandi et al 2013; Huang 2013; Khan et al 2009; Rocchetti et al 2008). Recent electron paramagnetic resonance (EPR) (James et al 2012), nuclear magnetic resonance (NMR) (Gustavsson et al 2013), and fluorescence resonance energy transfer (FRET) (Dong and Thomas 2014) studies have revealed that PLB is essentially a subunit of SERCA2a, remaining tightly bound even after phosphorylation (Fig. 1B).…”
Section: Introductionmentioning
confidence: 99%